The Effect of COVID-19 on inclusive mathematics education (Teacher Education through Flexible Learning in Africa (TETFLE), 2023)
The COVID-19 pandemic has dramatically changed education all over the world. As part of emergency remote teaching (ERT), the switch to online instruction had several technological, pedagogical and social challenges. Oral hearing impaired (HI) learners experienced difficulties during synchronous online lessons with hearing devices not picking up sounds, disruption to comprehend the lesson, not familiar with the online devices and emotional side-effects (Krishnan et al., 2020). The research question that guided this study is what is the influence of COVID-19 on mathematics teachers’ inclusive practices for oral HI learners? This study followed a case study design and collected data from two high school inclusive mathematics teachers before the pandemic and during ERT. The South African Department of Basic Education’s (DBE, 2011) Guidelines for responding to learner diversity in the classroom through curriculum and assessment policy statements and Whittle, Tiwari, Yan and Williams’ (2020) ERT environment framework’s design step guided the data collection and analysis processes. Data was collected in the form of interviews, observations and document analysis. It was found that teachers should receive adequate training when teaching in an inclusive school focusing on hearing impairments. During ERT the teachers felt teaching became a 24-hour job, the school’s expectations were high and they had strict requirements on the appearances of the videos. They had to produce between 12 and 16 videos per week for asynchronous teaching. Hardly any inclusive practices were implemented during ERT. The HI learners were neglected during the lockdown of schools during the COVID-19 pandemic as the teachers only focussed on making videos and tried to cope with the demands. More research needs to be done to determine how the COVID-19 pandemic, and possible future pandemics, and lack of inclusive practices influence the HI learners’ understanding and progression in mathematics. From that a framework can then be constructed to guide inclusive teachers in possible future pandemics and ERT scenarios.
Keywords: Inclusive education; mathematics; hearing impaired learners; differentiation; emergency remote teaching; COVID-19; online learning